APPRAISAL OF MANAGEMENT PRACTICES OF NATIONAL EXAMINATIONS COUNCILIN NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The purpose of the study was to appraise the management practices of NationalExaminations Council (NECO) on personnel, infrastructural and financial management ofCouncil fund. Three research questions and three null hypotheses guided the study. Thepopulation were 154NECO Senior administrative staff and 44Heads of Departmentmakinga total of 198 respondents. There was no sampling carried out because the populationwas small so the entire population was used. The design of the study was a descriptivesurvey. The research instrument was a questionnaire titled “Appraisal of Managementpractices questionnaire (AMPQ) and was validated by experts. The instrument wasassessed for reliability using internal consistency of Cronback Alpha method. Thereliability coefficient obtained yielded 0.92. The data obtained were organized andanalyzed using the mean and standard deviation to answer research questions and t-testto test the null hypotheses. Some of the major finding revealed that NECO managementadhered to the regulation system (manual) in the personnel, infrastructural, and financialmanagement of the Council. The hypotheses tested indicated no significant difference inthe mean rating of both NECO senior administrative staff and heads of Department on theextent to which NECO management adhered to the regulation system (manual) onpersonnel, infrastructural and financial management ofthe Council. Based on the findings,the researcher recommended that NECO management should continue to be guided byNECO rules and regulation in personnel, infrastructural and financial management of theCouncilamong others.